The effects of stirring speed and reinforcement particles on porosity formation in cast MMC - Aqida, S. N.; Ghazali, M. I.; Hashim, J. (Faculty of Mechanical Engineering, 2003)
This study on porosity in cast metal matrix composite (MMC) was particular to discontinuous silicon carbide particles reinforced aluminium silicon alloy. Stir casting with three different stirring speeds and weight percentage of silicon carbide particles were applied to cast the specimens for porosity measurement. The results were measured from samples of 100, 200 and 500 rpm of stirring speed as well as from the effect of reinforcing silicon carbide particles in aluminium silicon alloy at 0, 5, 10 and 15%. Clustering particles at 100 rpm stirring speed tempted porosity formation among the reinforcement particles. At 200 rpm, the MMC contained less porosity as particles were distributed quite uniformly compared to the 100 rpm stirred sample. At 500 rpm, the MMC contained higher porosity, where entrapment of gas occurred more during stirring. However, the silicon carbide particles were distributed uniformly. Porosity presence was at least 0.09% in un-reinforced alloy stirred at 200 rpm while the highest content of porosity, 15.28%, was measured in 500 rpm reinforced specimen.